Optimum maternal healthcare service utilization and infant mortality in Ethiopia - Kiross, Girmay Tsegay (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Ethiopia has one of the highest rates of infant mortality in the world. Utilization of maternal healthcare during pregnancy, at delivery, and after delivery is critical to reducing the risk of infant mortality. Studies in Ethiopia have shown how infant survival is affected by utilization of maternal healthcare services, however, no studies to date have investigated the relationship between optimum utilization of maternal healthcare services utilization and infant mortality. Therefore, this study examined the effect of optimum utilization of maternal healthcare service on infant mortality in Ethiopia based on the World Health Organization (WHO, 2010) guidelines. METHODS: We used nationally representative cross-sectional data from the Ethiopian Demographic and Health Survey (EDHS). Sampling weights were applied to adjust for the non-proportional allocation of the sample to the nine regions and two city administrations as well as the sample difference across urban and rural areas. A total of 7193 most recent births from mothers who had provided complete information on infant mortality, ANC visits, tetanus injections, place of delivery and skilled birth attendance during pregnancy were included. The EDHS was conducted from January to June 2016. We applied a multivariate logistic regression analysis to estimate the relationship between optimum maternal healthcare service utilization and infant mortality in Ethiopia. RESULTS: The findings from this study showed that optimum maternal healthcare service utilization had a significant association with infant mortality after adjusting for other socioeconomic characteristics. This implies that increased maternal healthcare service utilization decreases the rate of infant mortality in Ethiopia. The main finding from this study indicated that infant mortality was reduced by approximately 66% among mothers who had high utilization of maternal healthcare services compared to mothers who had not utilized maternal healthcare services (AOR = 0.34; 95%CI: 0.16–0.75; p-value = 0.007). Furthermore, infant mortality was reduced by approximately 46% among mothers who had low utilization of maternal healthcare services compared to mothers who had not utilized any maternal healthcare services (AOR = 0.54; 95%CI: 0.31–0.97; p-value = 0.040). CONCLUSIONS: From this study, we concluded that optimum utilization of maternal healthcare services during pregnancy, at delivery and after delivery might reduce the rate of infant mortality in Ethiopia.